A Late Pleistocene Guloninae (Carnivora, Mustelidae) from South America (Argentina, Entre Ríos province), biogeographic implications. (October 2017) - Schiaffini, Mauro I.; Prevosti, Francisco J.; Ferrero, Brenda S.; Noriega, Jorge I.
Abstract: The record of Guloninae presents mainly a Holarctic distribution, with only Eira barbara occurring in South America (SA). This lineage immigrated from Central America at least in the Pleistocene. The fossil record of Guloninae for SA is limited to a few known specimens of Eira from Late Pleistocene of Brazil. We report a new specimen of E . barbara (an upper carnassial) from Late Pleistocene of Entre Ríos, Argentina. We also discuss the taxonomic assignation of this new fossil and its paleoenvironmental relevance using Species Distribution Modeling (SDM). The new material comes from Ensenada Creek, Salto Ander Egg Formation, from the Late Pleistocene between 120 and 60 ky BP. The locality is farther south than its recent distribution, and SDM shows low suitability values for such area, which also indicates that the species is absent from this area in present time. The P4 is bigger and the protocone has a more anterior position relative to the paracone than that of recent specimens of E . barbara . This new fossil indicates that E . barbara had a wider distribution over the Late Pleistocene and, if our interpretation is correct, it has been present in SA at least since 120-60 ky BP. The presence of E . barbara in such a southern locality, together with other taxa recorded in this site and the associated geological and paleoenvironmental evidences, indicates warmer and more humid conditions, compared with the current conditions, which might have allowed a southern displacement of taxa more related to forested and tropical environments. Highlights: New fossil material from South America assigned to Guloninae are presented. The tayra was well extended across South America by Late Pleistocene. Warmer and humid climate for last Interglacial in southern South America is inferred.